2018
DOI: 10.1111/spol.12469
|View full text |Cite
|
Sign up to set email alerts
|

From quasi‐markets to public–private networks: Employers' engagement in public employment services

Abstract: This article explores the implications of creating a role for private-sector partners in public employment services (PES), rather than creating quasi-markets. It focuses on how the engagement of employers in public-private networks with local government can enhance employment opportunities for disadvantaged welfare recipients but may require a further shift in local public services. The theory relates to contractual arrangements versus network modes of publicprivate partnerships. Based on surveys among employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(130 reference statements)
1
11
0
Order By: Relevance
“…In contrast to the discussion of stimulation recruitment for workers with difficulties in finding employment, there are many papers discussing the potential of network modes of public-private partnerships for public employment services (PES). van Gestel, Oomens, and Buwalda write about innovative and promising cases of public-private networks in employment services [19]. The authors show that under certain conditions vulnerable job seekers are better served by a network (government and non-government structures) involving employers than by a standard employer-government employment service-based approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to the discussion of stimulation recruitment for workers with difficulties in finding employment, there are many papers discussing the potential of network modes of public-private partnerships for public employment services (PES). van Gestel, Oomens, and Buwalda write about innovative and promising cases of public-private networks in employment services [19]. The authors show that under certain conditions vulnerable job seekers are better served by a network (government and non-government structures) involving employers than by a standard employer-government employment service-based approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These various types of employer engagement also involve different roles of employers (Van der Aa and Van Berkel, 2014;Ingold, 2018;Orton et al, 2018;Van Gestel et al, 2019). When the focus is on employers' recruitment needs, employers are seen as Employer Engagement towards Jobseekers with Disabilities customers of employment support agencies.…”
Section: Employer Engagement In Activation Policiesmentioning
confidence: 99%
“…Research also revealed that employers may find ways to skirt regulations: they have leeway in dealing with institutional pressures (Boon et al, 2009;Van Gestel and Nyberg, 2009). Finally, there is some evidence suggesting that it cannot be taken for granted that employment support agencies or employers are ready and willing to perceive their own and each other's role as that of partner (Orton et al, 2018;Van Gestel et al, 2019).…”
Section: Employer Engagement In Activation Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They decide how to post vacancies, whom to recruit and whom to dismiss. In recent years, there has been a growing research interest in the role, the engagement and the responsibility employers have in relation to activation policies as well as labour market integration and retention of disadvantaged groups (e.g., Lindsay & McQuaid, 2009; van Gestel et al, 2019). This has been characterised as shift from a supply side focus (making job seekers ready for jobs) to a demand side focus (making employers ready for jobseekers) (Bredgaard, 2018; Dinan, 2019; Ingold, 2020; Ingold & Stuart, 2015).…”
Section: Introductionmentioning
confidence: 99%